Acceptability of smartphone applications for facilitating layperson naloxone administration during opioid overdoses. Issue 1 (4th December 2019) - Marcu, Gabriela; Aizen, Roy; Roth, Alexis M; Lankenau, Stephen; Schwartz, David G
Abstract: Objective: We investigated user requirements for a smartphone application to coordinate layperson administration of naloxone during an opioid overdose. Materials and Methods: We conducted interviews and focus groups with 19 nonmedical opioid users and other community members in the Kensington neighborhood of Philadelphia, Pennsylvania, which has one of the highest overdose rates in the country. Data were analyzed using thematic analysis. Results: We found high levels of trust and reliance within one's own social group, especially nonmedical opioid users and members of the neighborhood. Participants distrusted outsiders, including professional responders, whom they perceived as uncaring and prejudiced. Participants expressed some concern over malicious use of a location-based application, such as theft when a victim is unconscious, but overall felt the benefits could outweigh the risks. Participants also trusted community-based organizations providing services such as bystander training and naloxone distribution, and felt that a smartphone application should be integrated into these services. Discussion: Individuals affected by opioid use and overdose reacted positively to the concept for a smartphone application, which they perceived as a useful tool that could help combat the high rate of opioid overdose fatalities in their neighborhood. A sense of unity with others who have shared their experiences could be leveraged to connect willing bystanders with victims of overdose, but risk must be mitigated for layperson responders. Conclusion: Based on participant experiences with overdoses, trust-based considerations for the design of smartphone applications to facilitate layperson response will be critical for their adoption and use in real overdose situations.